Equine bone marrow-derived mesenchymal stromal cells are heterogeneous in MHC class II expression and capable of inciting an immune response in vitro - Schnabel, Lauren V (BioMed Central, 2014)
INTRODUCTION: The horse is a valuable species to assess the effect of allogeneic mesenchymal stromal cells (MSCs) in regenerative treatments. No studies to date have examined recipient response to major histocompatibility complex (MHC)-mismatched equine MSCs. The purposes of this study were to immunophenotype MSCs from horses of known MHC haplotype and to compare the immunogenicity of MSCs with differing MHC class II expression. METHODS: MSCs and peripheral blood leukocytes (PBLs) were obtained from Thoroughbred horses (n = 10) of known MHC haplotype (ELA-A2, -A3, and -A9 homozygotes). MSCs were cultured through P8; cells from each passage (P2 to P8) were cryopreserved until used. Immunophenotyping of MHC class I and II, CD44, CD29, CD90, LFA-1, and CD45RB was performed by using flow cytometry. Tri-lineage differentiation assays were performed to confirm MSC multipotency. Recombinant equine IFN-γ was used to stimulate MHC class II negative MSCs in culture, after which expression of MHC class II was re-examined. To assess the ability of MHC class II negative or positive MSCs to stimulate an immune response, modified one-way mixed leukocyte reactions (MLRs) were performed by using MHC-matched and mismatched responder PBLs and stimulator PBLs or MSCs. Proliferation of gated CFSE-labeled CD3+ responder T cells was evaluated via CFSE attenuation by using flow cytometry and reported as the number of cells in the proliferating T-cell gate. RESULTS: MSCs varied widely in MHC class II expression despite being homogenous in terms of “stemness” marker expression and ability to undergo trilineage differentiation. Stimulation of MHC class II negative MSCs with IFN-γ resulted in markedly increased expression of MHC class II. MLR results revealed that MHC-mismatched MHC class II-positive MSCs caused significantly increased responder T-cell proliferation compared with MHC-mismatched MHC class II-negative and MHC-matched MSCs, and equivalent to that of the positive control of MHC-mismatched leukocytes. CONCLUSIONS: The results of this study suggest that MSCs should be confirmed as MHC class II negative before allogeneic application. Additionally, it must be considered that even MHC class II-negative MSCs could upregulate MHC class II expression if implanted into an area of active inflammation, as demonstrated with in vitro stimulation with IFN-γ.